THU0275 Pharmacodynamic Modeling of BTK Occupancy versus Efficacy in RA and SLE Models Using The Novel Specific BTK Inhibitor M2951. (15th July 2016) - Haselmayer, P.; Camps, M.; Liu-Bujalski, L.; Morandi, F.; Head, J.; Zimmerli, S.; Bruns, L.; Bender, A.; Schroeder, P.; Grenningloh, R.
Abstract : Background: Bruton's tyrosine kinase (BTK) is a clinically proven target in several hematological indications. Due to its role in mediating the signaling of both B cell receptors (BCR) and Fc receptors (FcR), BTK is also a potential target for the treatment of autoimmune disease such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), where B cell and innate immune cell activation are key drivers of pathology. Objectives: We are developing M2951, a novel, highly selective BTK inhibitor that is suitable for the treatment of chronic diseases. This work aimed at characterizing its efficacy in various cellular assays in vitro as well as in disease models for RA and SLE. Based on in vivo efficacy and target occupancy data, a PKPD model describing the correlation of BTK inhibition and disease severity reduction was built. Methods: The BTK inhibitor M2951 was characterized in various biochemical and cellular assays to demonstrate its potency and specificity. To determine disease-modifying activity, M2951 was tested in NZB/W F1 mice which had been infected with e replication-deficient adenovirus expressing IFN-alpha in order to synchronize disease onset. Efficacy was determined by measuring proteinuria and histological kidney damage. Furthermore, M2951 was tested in a collagen-induced arthritis model (CIA) in the mouse. Paw scores were used to measure efficacy. A biochemical assay was developed that allowed to measure the degree of BTK occupancy in blood cells and splenocytes was developed. This assay was used to build a translational PKPD model linking target occupancy to efficacy. Results: M2951 potently inhibits BCR- and FcR-mediated signaling and subsequent activation and function of B cells and certain myeloid cells. In mouse models of RA and SLE, M2951 displayed robust efficacy as demonstrated by a marked reduction of disease severity. In the NZB/W F1 IFN-α-accelerated SLE model, efficacy correlated with B cell inhibition, reduction of autoantibodies, and decreased circulating memory B and T cells. In addition to SLE, RA-like symptoms were inhibited in a collagen-induced arthritis model. In order to translate preclinical efficacious doses to humans, we determined the degree of target occupancy necessary to achieve disease reduction. Pharmacodynamic modeling showed that BTK occupancy of 60 and 80% was linked to 80% and near complete disease inhibition, respectively, in both the RA and SLE models. Conclusions: In summary, these results demonstrate the potential of M2951 to treat autoimmune disease and may inform rational dose decisions as M2951 is advanced for development in rheumatologic diseases. Disclosure of Interest: P. Haselmayer Employee of: Merck KGaA, M. Camps Employee of: Merck Serono, L. Liu-Bujalski Employee of: EMD Serono, F. Morandi Employee of: EMD Serono, J. Head Employee of: EMD Serono, S. Zimmerli Employee of: EMD Serono, L. Bruns Employee of: Merck KGaA, A. Bender Employee of: EMD Serono, P. Schroeder Employee of: EMD Serono, R. Grenningloh Employee of: EMD Serono